1981
DOI: 10.1111/1523-1747.ep12479347
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiology of the Skin: Review of Some Effects on Epidermis and Hair

Abstract: Significant doses of ionizing radiation produce an acute skin reaction characterized by erythema, epilation, and dry or moist desquamation with or without erosions. These early acute changes are dose-dependent and reflect damage to the germinative cells of the epidermis and to the cutaneous vasculature. Studies in the pig, for example, have shown that the degenerative phase of cell loss (2-3 weeks) results from reproductive failure in germinative cells and a sharp reduction in the proliferation rate of basal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 18 publications
1
59
0
2
Order By: Relevance
“…Mitotic activity in the germinal cells of the sebaceous glands, hair follicles, and epidermis is inhibited, and basal layer stem cells are depleted. 9,19,29,41 Prostaglandins and thiol compounds are potentially radioprotective agents that have been used to protect normal tissue, with varying degrees of success. In animal models, both have been used to protect hair follicles and other skin structures.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Mitotic activity in the germinal cells of the sebaceous glands, hair follicles, and epidermis is inhibited, and basal layer stem cells are depleted. 9,19,29,41 Prostaglandins and thiol compounds are potentially radioprotective agents that have been used to protect normal tissue, with varying degrees of success. In animal models, both have been used to protect hair follicles and other skin structures.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Zhong et al [7] stated that the \integrated microbeam doses, (which for low valley doses) can be approximated as the in-beam dose times the ratio of the beam width to beam spacing". There exists a vast body of literature over several decades on the acute effects of radiation therapy on skin tissue (radiodermatitis), some of which have been documented in review articles [14,15] and text books [16][17][18][19]. McKee et al [20] state:…”
mentioning
confidence: 99%
“…Moreover, large number of langerhans cells was present in irradiated rat skin and disappeared with topical treatment. Studies in the pig skin, showed that postregenerative phase of hyperplasia reflect a temporary overshoot of cell density above control levels; a subsequent decrease in hyperplasia indicates feedback control of cellular proliferation 14 . Collagen is known to constitute 70% of dry skin mass, which is either collagen type I, III and VI.…”
Section: Discussionmentioning
confidence: 99%